2022
DOI: 10.1038/s41598-022-12143-2
|View full text |Cite
|
Sign up to set email alerts
|

Human induced mesenchymal stem cells display increased sensitivity to matrix stiffness

Abstract: The clinical translation of mesenchymal stem cells (MSCs) is limited by population heterogeneity and inconsistent responses to engineered signals. Specifically, the extent in which MSCs respond to mechanical cues varies significantly across MSC lines. Although induced pluripotent stem cells (iPSCs) have recently emerged as a novel cell source for creating highly homogeneous MSC (iMSC) lines, cellular mechanosensing of iMSCs on engineered materials with defined mechanics is not well understood. Here, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Stem cells, known for their unique self-renewal and differentiation capabilities, are at the forefront of research interest. However, a significant challenge in the field remains the precise control over stem cell growth and differentiation. , The cellular behavior is profoundly influenced by the multifaceted extracellular matrix (ECM) environment, encompassing factors such as the ECM protein concentration and various stimuli from the stem cell niche. These stimuli include both chemical cues, ,, such as composition ,,,,, and ligand density, and physical factors like matrix stiffness, surface topography, ,, and interfacial hydrophobicity .…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells, known for their unique self-renewal and differentiation capabilities, are at the forefront of research interest. However, a significant challenge in the field remains the precise control over stem cell growth and differentiation. , The cellular behavior is profoundly influenced by the multifaceted extracellular matrix (ECM) environment, encompassing factors such as the ECM protein concentration and various stimuli from the stem cell niche. These stimuli include both chemical cues, ,, such as composition ,,,,, and ligand density, and physical factors like matrix stiffness, surface topography, ,, and interfacial hydrophobicity .…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture: Human iMSCs were derived and characterized as previously described. [5,43] For all studies, aliquots of cell suspension were seeded to the PMCC-coated ITO glasses placed in ultra-low attachment plates (Fisher Scientific) at a density of ≈1000-10 000 cells cm −2 . To study attachment and proliferation, cells were cultured in an expansion medium, consisting of high-glucose KnockOut Dulbecco's modified Eagle's medium (DMEM; Gibco) supplemented with 20% (v/v) HyClone fetal bovine serum (FBS; GE Healthcare Life Sciences), beta-fibroblast growth factor (1 ng mL −1 ; Invitrogen), nonessential amino acids (0.1 mm; Gibco), GlutaMAX (2 mm; Gibco), beta-mercaptoethanol (0.1 mm; Gibco), and antibiotic-antimycotic (100 U mL −1 ; Gibco), while to study osteogenic differentiation cells were cultured in the commercially available OsteoLife Complete Osteogenesis Medium (Lifeline Cell Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…[1] In particular, tissue stiffness controls cell adhesion, migration, and proliferation, and acts as a strong driver for phenotypic commitment both in vivo and in vitro. [2][3][4][5] For example, atop soft hydrogels that mimic the stiffness of brain tissue, mesenchymal stem cells (MSCs) express neuronal biomarkers, whereas on rigid substrates they produce osteocalcin, a bone tissue-specific protein. [4] So far, most of the investigations focused on understanding the effect of stiffness on cell behavior and differentiation rely on substrates having stiffness values ranging from kPa to a few MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological results showed that the hMSC morphology generally tended to have an elongated and flattened shape, characterized by high anisotropy, high aspect ratio, and low circularity. 107,108 Most of the induced cells grew to be cuboidal in shape, showing low anisotropy, a low aspect ratio, and high circularity. 109,110 Few cells were induced to tend to the stellate morphology, exhibiting low anisotropy, a low aspect ratio, and moderate circularity.…”
Section: Biomaterials Science Papermentioning
confidence: 99%